(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Most selection problems are multi-decision and multi-criteria in nature. The group decision (GD) literature presents several methods for solving them. Most of them belong to utilities functions based class. However, the use of any one group decision method of this class for a specific problem is often not appropriate, given the characteristics of the latter. The objective of the present work is to compare four GD utility functions based methods, two of which are classical (Lon-Zo and MACASP) and two new (KEMIRA G-I and KEMIRA G-II), by examining their suitability for solving two multi-criteria choice problems, namely the selection of a crop variety adapted to the Centre-Est region of Burkina Faso and the selection of a site for the implementation of a waste incineration plant in the city of Vilnius in Lithuania. The results show that group decision methods based on aggregation utility functions are most suitable when the criteria are homogeneous (i.e. when criteria can compensate naturally). However, when the criteria are heterogeneous (i.e. when there is no natural compensation between criteria), these methods can still be successfully applied when the heterogeneous nature of the criteria is taken into account. This explains the good performance of the KEMIRA G-I and KEMIRA G-II methods, which take into account the heterogeneous nature of the criteria, compared with the Lon-Zo and MACASP methods, which do not.